A Case of Abdominal Abscess in Crohn’s Disease: Successful Endoscopic Demonstration of an Obscure Enteric Fistula by Dye Injection via a Percutaneous Drainage Catheter - Toshihide Hamada (Case Reports in Gastroenterology, 2009)
Abdominal and pelvic abscesses occur in approximately 10–30% of Crohn’s disease patients during the course of the disease; most of these abscesses have an enteric communication. For this condition, percutaneous abscess drainage (PAD) rather than emergency surgery has recently been recognized as a valuable procedure for initial treatment. However, in cases wherein the abscess is accompanied by an enteric fistula, the recurrence of abscess might be inevitable without the management of the enteric fistula. Therefore, demonstration and evaluation of the enteric fistula is essential to prevent abscess recurrence; however, this is not necessarily a simple procedure. Here, we report abdominal abscess accompanied by a rectal fistula in a patient with Crohn's disease; this condition was successfully treated by PAD. Furthermore, PAD was also useful in identifying the fistula by colonoscopy involving dye injection via the drainage catheter. To our knowledge, no previous literature has reported the use of dye injection via the drainage catheter for identifying a fistula during endoscopic examination. We present here the radiographic, sonographic, and endoscopic findings of this case.